A Giant Primary Retroperitoneal Serous Cystadenoma: Case Report and Review of Retroperitoneal Cysts - Mori, Amit; Changela, Kinesh; Alhankawi, Dhuha; Itskovich, Alexander; Butt, Ahmar; Reddy, Madhavi (The Surgery Journal, 2017)
Primary retroperitoneal serous cystadenomas (PRSCs) are rare cystic lesions whose pathogenesis is currently not well understood. Although the vast majority of tumors are benign, early recognition and resection is necessary to avoid malignant transformation, rupture, and secondary infection. Here we present the case of a 79-year-old woman who presented with confusion, visual hallucinations, and a history of fall. As part of the work-up for abdominal distension, computed tomography scan of the abdomen and pelvis was performed, which revealed a right-sided retroperitoneal cystic lesion measuring 26.6 × 16.7 cm in size. The lesion was resected laparoscopically, and the surgical specimen measured 28 × 17 cm. Histology revealed a serous cystadenoma. The postsurgical course was uneventful, and no radiological recurrence was noted on 3 months follow-up. Very few primary retroperitoneal cystic lesions have been reported in the literature. Most lesions are benign and predominantly occur in females. They may remain asymptomatic for long periods of time and are usually discovered when they reach very large in size. In rare cases, these lesions may have malignant potential. Diagnosis of PRSC should be considered in the differential diagnosis of all retroperitoneal cysts.
Keywords: primary; retroperitoneal; serous; cystadenomas; cystic